2011
DOI: 10.1186/1756-0500-4-165
|View full text |Cite
|
Sign up to set email alerts
|

Delay in diagnosis of tuberculosis in Rawalpindi, Pakistan

Abstract: BackgroundDelay in diagnosis and treatment of tuberculosis (TB) may enhance the chances of morbidity and mortality and play a key role in continuous transmission of the bacilli. The objective of this study was to describe health care seeking behavior of suspected TB patients and initial diagnostic work up prior to consultation and diagnosis at National TB Center (NTC).FindingsInterviews of 252 sputum smear positive patients were taken from NTC, Rawalpindi. The duration between on-set of symptoms and start of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
5
13
2
1
Order By: Relevance
“…Many authors have found higher diagnostic delay among pulmonary patients. 1,5,30 But, in accordance with some other studies 10,11,16 extra-pulmonary TB patients were significantly more likely to have experienced diagnostic delay. However, it is not surprising because, patients with extra-pulmonary TB may have diffuse or non-specific symptoms and are likely to experience longer delays than patients with pulmonary TB in both low and highendemic settings.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Many authors have found higher diagnostic delay among pulmonary patients. 1,5,30 But, in accordance with some other studies 10,11,16 extra-pulmonary TB patients were significantly more likely to have experienced diagnostic delay. However, it is not surprising because, patients with extra-pulmonary TB may have diffuse or non-specific symptoms and are likely to experience longer delays than patients with pulmonary TB in both low and highendemic settings.…”
Section: Discussionsupporting
confidence: 75%
“…13,14 In several studies, it has been documented that health seeking behavior, low access to health care facilities, poverty, rural residence, education, female sex, old age are in significant relation with delays in diagnosis. 1,5,15,16 Therefore, the authors have tried to find out the association between the various socio-demographic factors and delay in diagnosis among TB patients in Bangladesh context. In Bangladesh no recent study was available in this regard.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…21,22 We may thus have overestimated the extent of pre-treatment LTFU. There is no electronic database of patient records in the country and it was not feasible to manually review the treatment registers maintained in the hundreds of public sector facilities.…”
Section: Public Health Actionmentioning
confidence: 99%